Explorative Analysis of Bank Syariah Indonesia Youtube Channel - Furqonul Haq (AL-ARBAH: Journal of Islamic Finance and Banking, 2023)
Purpose - This research was conducted to qualitatively analyze the profile and columns on the Bank Syariah Indonesia (BSI) YouTube channel.Method - This research describes the BSI YouTube channel qualitatively with an exploratory approach.Result - The results showed that the BSI YouTube channel has a profile with 65.5K subscribers and 420 video posts. Posts on the BSI YouTube channel consist of video and image posts. The BSI YouTube channel has nine columns like most other YouTube channels. All columns (home, videos, shorts, live, playlist, community, channels, about and search) can be analyzed exploratively.Implication - The population in this study is the Youtube channel of Islamic banks. The sample used is the BSI Youtube channel.Originality- Research that qualitatively analyzes the YouTube channels of Islamic banks in Indonesia.